EVALUATION OF REAL NEEDS NUMBER FOR OPERATION AND MAINTENANCE OF DAMS IN BALI PROVINCE - Fransisca Natania Karina Rediasti; Ida Bagus Gede Indrayana; Kurniawan Putra Santoso (Universitas Udayana, 2024)
An increase in population by 1.04% and crop area by 14.08% in Bali Province, will also increase the water needs. Dam as water infrastructure that supports water availability, is needed in overcoming the problem. Dams require operation and maintenance (O&M) to keep function optimally. Operation and maintenance costs need to be evaluated periodically with the real needs of operation and maintenance. Real needs of operation and maintenance suitability can guarantee the optimal functioning of the dam. This study evaluated the suitability of Balinese dam’s operation and maintenance, namely Benel Dam, Telaga Tunjung Dam, Gerokgak Dam, and Palasari Dam. Dam performance appraisals include physical, operational security, and institutional ranging from 0 to 100. The results the grouped into good, enough, less, and bad category. All four dams got “enough”, so their real needs number for operation and maintenance need to be evaluated. The evaluation showed that Gerogkak Dam had the largest real needs number for operation and maintenance value, which is IDR 28,767,099,149. The real needs of operation and maintenance value is consisted of ≥ 90% dredging’s cost. Dredging’s cost us mainly influenced by sediment’s volume. So, to reduce sediment’s volume and improve dam’s performance for irrigation, it is necessary to increase the efficiency of dam’s operation and maintenance. Efficient dam operation also necessary due to the limited operators. Building efficiencies that control sediment and water supply, must be increase aligned with water needs and reservoir conditions.